Solid-liquid transition in Nb powder determined by third harmonic susceptibility - Oliveira, A. A. M.; Lisboa Filho, Paulo Noronha [UNESP]; Ortiz, W. A. (Elsevier B.V., 2008)
Measurements of the third harmonic of the AC-susceptibility were employed to determine the boundaries of the linear regime of the magnetic response of Nb powder. Non-linear contributions to the magnetic response reveal the occurrence of a structured phase, disappearing as the vortex lattice melts to the liquid state. A systematic study of the third harmonic was conducted to determine how its onset temperature depends on experimental parameters, such as the frequency and amplitude of the excitation field. The melting line (ML) has been extracted from the onset temperature measured at low-frequencies and low-excitation fields in the presence of DC magnetic fields. The study indicates that the ML can be described by a 3D vortex-glass model, except at lower fields, where the system experiences a depinning crossover, and the best description of the experimental data is provided by a 3D Bose-glass model. (c) 2008 Elsevier B. V. All rights reserved.
Keywords: third harmonic; melting line; niobium; depinning; vortex matter